Athletic Identity and Self-Esteem of Wheelchair Basketball Players - Kęstutis Skučas (Lithuanian Sports University, 2018)
Background.  Disabled  persons  do  not  consider  and  use  a  single  identity  to  represent  themselves. Athletic identity as a wheelchair basketball player can help the process of acceptance and support psychological adjustment. Thus, there is a need to research the association between and the influence of the wheelchair basketball player's qualification and a strong athletic identity on a person's self-esteem (Hawkins, Coffee, & Soundy, 2014; Martin, Adams-Mushett, & Smith, 1995). Methods. The multidimensional Athletic Identity Measurement Scale (Brewer & Cornelius, 2002) was used to assess self-identity, social identity, exclusivity and negative affectivity of 36 wheelchair basketball players. Self- esteem was evaluated by the adapted V. Stolin's (Столин, 1983) test including nine self-evaluation scales: internal integrity,  self-confidence,  self-direction,  self-image,  self-interest,  self-content,  self-orientation,  self-contradiction and self-accusation. Results.  It  was  found  out  that  the  athletic  identity  value  of  the  players  participating  in  international  level competitions (30 points) is statistically significantly higher compared to that of participating in national level events (18 points, p < .05). Conclusions. Disabled persons of the competition group with better athletic identity represented stronger self- integrity and were less self-accusative, more self-content, their self-confidence grew and they had a better self-image in comparison with the national level group. Keywords: self-confdence, self-image, persons with physical disability.